Model Kemitraan Kelompok Usaha Mikro Dengan Lembaga Keuangan Dalam Pemberdayaan Dan Penguatan Ekonomi Rumah Tangga - Johan Setiawan (JURNAL AGRIBISNIS TERPADU, 2019)
One business actor that has an important existence but is sometimes considered "forgotten" in the policy arena in this country is Micro, Small and Medium Enterprises (MSMEs). However, if we know more deeply and deeply, the role of Micro, Small and Medium Enterprises is not just a supporter of the contribution of the national economy. History has proven that Small and Micro Enterprises in Indonesia still exist and develop due to the economic crisis that occurred in 1997 that hit this country. It even became a rescue valve and contributed significantly to income and employment.The role of the government is very important to support and encourage financial institutions and SOEs to help the progress of the small and medium business sector, financial institutions must provide space for productive and creative housewives who have businesses in an effort to meet household needs while helping their husbands in efforts to strengthen the home economy stairs, the space is in the form of an easy and inexpensive credit or financing scheme that can be accessed by housewives.